2018
DOI: 10.1007/s11145-018-9924-8
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between reading and listening comprehension: shared and modality-specific components

Abstract: This study aimed to increase our understanding on the relationship between reading and listening comprehension. Both in comprehension theory and in educational practice, reading and listening comprehension are often seen as interchangeable, overlooking modality-specific aspects of them separately. Three questions were addressed. First, it was examined to what extent reading and listening comprehension comprise modality-specific, distinct skills or an overlapping, domain-general skill in terms of the amount of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
57
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(64 citation statements)
references
References 57 publications
(94 reference statements)
5
57
0
2
Order By: Relevance
“…Consistent with our expectations, vocabulary was the strongest contributor to listening comprehension, and it was even the only direct contributor. This finding underscores the importance of vocabulary knowledge in constructing a situation model (Kintsch & Rawson, 2005;van den Broek et al, 1995) and relates to previous findings that confirm this conceptual relationship with empirical data (Hagtvet, 2003;Kim, 2016;Kim & Phillips, 2014;Lepola et al, 2012;Lervåg et al, 2018;Protopapas et al, 2013;Wolf et al, 2019;Wolfgramm et al, 2016). This contribution seems to remain strong, as our multigroup analysis showed that the contribution of vocabulary was even stronger for the 11-to 12-year-olds than for the 9-to 10-year-olds.…”
Section: Discussionsupporting
confidence: 87%
“…Consistent with our expectations, vocabulary was the strongest contributor to listening comprehension, and it was even the only direct contributor. This finding underscores the importance of vocabulary knowledge in constructing a situation model (Kintsch & Rawson, 2005;van den Broek et al, 1995) and relates to previous findings that confirm this conceptual relationship with empirical data (Hagtvet, 2003;Kim, 2016;Kim & Phillips, 2014;Lepola et al, 2012;Lervåg et al, 2018;Protopapas et al, 2013;Wolf et al, 2019;Wolfgramm et al, 2016). This contribution seems to remain strong, as our multigroup analysis showed that the contribution of vocabulary was even stronger for the 11-to 12-year-olds than for the 9-to 10-year-olds.…”
Section: Discussionsupporting
confidence: 87%
“…Before conducting the experiment, pupils were screened for comprehension problems that could influence the study outcomes. Given the association between listening and reading comprehension (Wolf et al, 2019), a measure of reading comprehension was used for this purpose.…”
Section: Methodsmentioning
confidence: 99%
“…They also found that the reading comprehension advantage gradually decreases between 2nd and 6th grade as listening and reading comprehension become more interrelated. Moreover, Wolf et al [129] found that in 1st and 2nd graders, 34 and 40% of the variance in listening and reading comprehension was explained by the other comprehension type. This suggests that comprehension taps a general comprehension process, regardless of the comprehension modality.…”
Section: Discussionmentioning
confidence: 99%